Pola Sebaran Jenis Burung Paruh Bengkok Di Hutan Malagufuk Distrik Makbon Kabupaten Sorong - Maya Pattiwael; Charliany Hetharia (Universitas Muhammadiyah Sorong, 2023)
The distribution of parrots in Indonesia, one of which can be found in West Papua, precisely in the Malagufuk forest area, Sorong Regency. These types are also usually used as objects of observation by tourists. To complete the data on parrots in the Malagufuk forest, it is necessary to conduct research, both on their species and their distribution patterns, so that later this data can become a reference in efforts to protect and preserve these species, considering that this bird species is still included in the bird list vulnerable to extinction. The Point of Abundance Index (IPA) or point count is used as a method in this study, using 4 path observations with a length of 1000 meters each, distance between count points of 100 m and a circle diameter of 50 meters. Observation time is 20 minutes for each circle or counting point, which is carried out at 06.00 to 09.00 WIB and 15.00 to 17.00 WIB. The Morisita index (Id) is used to analyze the pattern of distribution of parrot species. There were 5 types of parrots from 3 families found at the study site, namely the rainbow lorikeet (Trichoglossus haemadotus) and parrot parrot (Eclectus roratus) from the Psittacidae family, the yellow-crested cockatoo (Cacatua galerita) and the king's cockatoo (Probosciger atterimus) from the family Cacatuidae and the Ambon king parrot (Alisterus amboinensis) from the Psitaculidae family. The results of the distribution pattern analysis using the Morisita Index (Id) means that there are 4 types of parrots whose distribution pattern is grouped while 1 other species cannot be analyzed because it only covers 1 individual.